1994
DOI: 10.1080/01635589409514300
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of food aversions in cancer patients during treatment

Abstract: Food aversions are a common complication of cancer treatment. This study evaluated an approach for blocking the formation of aversions to dietary items in 209 cancer patients treated with chemo- and/or radiotherapy. Patients were exposed to a sensory stimulus (fruit beverage, halava, odor) before initial treatments to provide a target for aversion formation, thereby sparing dietary items. Patients who developed an aversion to the "scapegoat" stimulus experienced a statistically significant 30% reduction in die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Furthermore, since pregnant women probably consume several foods or drinks in the hours preceding the onset of nausea, interference may limit the degree to which any single item becomes aversive (cf. Mattes, 1994).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, since pregnant women probably consume several foods or drinks in the hours preceding the onset of nausea, interference may limit the degree to which any single item becomes aversive (cf. Mattes, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…For example, nearly half of patients receiving repeated infusions of chemotherapy for breast cancer developed at least one aversion to an item in their normal diet (Jacobsen et al, 1993). However, the formation of learned food aversions to normal dietary items is diminished if an interference food is presented prior to the illness (Mattes, 1994). It is also suggested that foods high in protein, and those with strong odours such as coffee, may be particularly salient targets for aversion formation as a result of their flavour properties (Mattes et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…A similar learning process may occur in cancer patients because they often show learned avoidance to foods, or even environmental stimuli, associated with chemotherapy (Mattes et al, 1991;Mattes, 1994;Matteson et al, 2002). In laboratory animals learned flavour aversion produced by emetogenic treatments, including cytotoxic chemotherapy agents, can be blocked by anti-emetic medications.…”
Section: Conditioned Flavour Avoidance (Cfa)-manymentioning
confidence: 99%
“…species show CFA or learned flavour aversion to foods or flavours associated with toxicosis, including humans (Mattes et al, 1991;Mattes, 1994). CFA is used extensively to study malaise in laboratory animals, particularly the rat.…”
Section: Conditioned Flavour Avoidance (Cfa)-manymentioning
confidence: 99%
“…Broberg and Bernstein (1987) found that using strongly flavoured candies as scapegoats reduces food aversions during chemotherapy and, thereby, increases food consumption among paediatric patients. Furthermore, Mattes (1994) showed that patients exposed to a particular sensory stimulus demonstrate a statistically significant 30% reduction in the development of food aversion compared with the non-exposed patients.The elderly and undernutrition. In addition to application to cancer patients under chemotherapy, the study of food aversions and preferences has other interesting biomedical applications, particularly in the hospitalized elderly.…”
mentioning
confidence: 99%